CURRENT PROBLEMS OF THE TECHNOLOGY OF RED TABLE DRY WINES IN THE CONDITIONS OF CLIMATE CHANGE - O. Tkachenko; V. Larin (Harčova Nauka ì Tehnologìâ)
Production and demand for red table dry wines is stable. Climate change is one of the main factor in the annual variation of the total volume of wine produced in the world. Minimizing the impact of climate change on the quality characteristics of wine is a strategic direction of research at OIV. This work is devoted to the literary review of the current problems of the technology of red table dry wines in the conditions of climate change over the last 10 years. It was established that the increase in average annual temperature in comparison with the pre-industrial period is from 0.8 to 1.2°C. In addition, a decrease in precipitation during the grape growing season is predicted. Those regions that are currently considered cool will become suitable for growing grapes. Thus, it is possible to lose the typicality of wines from traditional wine-growing regions. Acceleration of ripening leads to the accumulation of high sugar content, high pH, low acidity, modification of varietal aromatic compounds, changes in the timing of phenolic ripening, and a general decrease in yield. Water stress increases the content of tannins and anthocyanins, negatively affects productivity. An increase in carbon dioxide content leads to a decrease in the concentration of anthocyanins and the intensity of color. Exposure to ultraviolet radiation contributes to the accumulation of more anthocyanins, quercetin and trans-resveratrol. Short-term and long-term adaptation strategies to climate change conditions are implemented to obtain high-quality grapes. The most important aspect is the reduction of alcohol content. Different techniques of maceration affect the organoleptic characteristics and the phenolic complex. It is promising to use non-Saccharomyces yeast to reduce alcohol content and form organoleptic characteristics and phenolic complex. The choice of stabilizing materials affects the phenolic composition and color stability. Aging techniques affect the phenolic complex and organoleptic characteristics. The current problems of technology are focused on preserving the quality and typicality of wine styles and at the same time take into account the changing taste preferences of consumers.